Penerapan K-Nearest Neighbor dalam Pendeteksian Abcessus - Puji Sari Ramadhan (Universitas Islam Sumatera Utara, 2019)
Abcessus is a collection of neutrophils that do not function anymore and have accumulated in tissue cavities infected with bacteria or parasites. This disease will cause swelling in the part of the skin tissue that contains pus and blood, this is due to the spread of skin tissue with staphylococcus aureus bacteria. The spread of infections carried out by bacteria will result in the release of toxins that cause inflammation and increase blood flow in the infected place. The high circulation of the disease among the community requires a concept of knowledge and information which can later be disseminated to the community so that it can reduce the risk of spreading this disease and can be done as soon as possible early treatment of people suffering from Abcessus. The concept of knowledge that will be formed is by transferring all forms of information and knowledge about Abcessus into the diagnosing application by applying the Expert System science that uses K-Nearest Neighbor analysis, later the method can produce the probability value or probability of diagnosing Abcessus for the symptoms that are felt clinically, of course, the knowledge and probability value of Abcessus will first be determined by an expert or expert in identifying the Abcessus. With the construction of diagnostic applications this can be used as a source to be used by the wider community in dealing with problems regarding diagnosis and knowledge of Abcessus, besides that it can also be used in the analysis of diagnostic conclusions by health or medical officers